Prototype of a Parental Robot for Child Safety - Delgado-Aleman, Rodrigo; Montenegro-Gonzales, Orlando; Rodriguez-Lopez, Elizabeth; Ordoñez-Paredes, Paul; Ponce-Puma, Johan; Esquicha-Larico, Elias; Mamani-Machaca, Elizabeth (LACCEI, 2024)
In today’s digital age, children’s exposure to electronic devices poses significant challenges in terms of safety and parental control. This article presents a solution to address these challenges through a modular and interactive device specifically designed to monitor and manage children’s use of technology. This proposal combines facial recognition, real-time monitoring and a reward system to promote positive behaviors, providing constant and educational supervision. The features and advantages of this parental robot are discussed in detail, highlighting its ability to improve digital safety and parental control. Previous studies and current trends in the market for parental control technologies are reviewed, emphasizing the growing need for adaptive and effective solutions in this field. The practical implications and potential benefits of implementing this device in family and educational contexts are also explored, demonstrating how it can contribute to a safer and more responsible technology use experience for children.